Riesgo psicológico y desórdenes musculoesqueléticos relacionado con riesgo ocupacional. (2024)
Musculoskeletal disorders (MSD) related to stress constitute one of the major health problems in the world; due to the strong impact on the physical, psychological and functional conditions of the worker the quality of life is considerably altered generating an important cost for the employer as well as for the employee. Objective: To evaluate epidemiologically the designs aimed at studying the relationship between psychological stress and diseases known as musculoskeletal disorders. Materials and methods: Based on bibliographic research in databases such as scopus, publindex, sispro and EBSCOhost, 4 articles were chosen for analysis out of a total of 7; the standardized Nordic questionnaire was used as measurement instruments and self-administered in a population that was subsequently subjected to standardized clinical examinations by occupational physicians. Results: it is determined that in 95% of the cases presented in each study there is a direct link between psychological stress and diseases with musculoskeletal disorders. It is concluded that the pathology with the highest incidence is lumbar disorder, with age being a factor of high prevalence between the range of 50 to 65 years of age, where there is a greater loss of working capacity. Conclusion: Psychosocial risks are directly associated with the generation of musculoskeletal problems in the working population.